The Absolute and Relative Quality of the Namibian Secondary Education: A distributional approach on grade 12 (NSSCH) performance - Sartorius von Bach, HJ; Kalundu, KM (Namibian Journal for Research, Science and Technology, 2020)
The Namibian independence in 1990 imparted a massive challenge to reform education and to refresh the system. Each child had to receive a fair chance to succeed in secondary education, fostering the country’s human-capital formation to improve economic performance. In this study uses data from 1996 to 2018 period to analyse the Secondary Education system in order to determine the systems’ progress by hypothesizing that educational output is attributed to spatial location, resource allocation and other opportunities. Results show that on a national basis, the average student performance declined. On regional level, results reveal that, (i) general access to secondary education improved significantly, (ii) the educational level of secondary education as reflected in the student points declined continuously, (iii) the narrowing performance variation did not contribute to the national goals, and (iv) that further attention is required to reach the goal of educational democracy. The findings give signals to the need that should urgently assess the drivers of human capital that enables the links secondary education output to economic achievements. On a macro level, the paper shows that, after two decades, the education reform slowly started to show positive results. Meanwhile, on a micro level, the analysis showed that both types of schools and educational support per student explain the level of secondary educational output, which would result into human capital.